ARTIFICIAL INTELLIGENCE TECHNOLOGIES AS A MEANS OF DEVELOPING STUDENTS’ TALENT IN RESEARCH WORK - Bozhko , Inna (Distance Education in Ukraine: Innovative, Normative-Legal, Pedagogical Aspects, 2025)
The article discusses the potential of artificial intelligence (AI) technologies to support and develop students’ talent in the process of research. The main AI tools that can be used in schools are analysed, and their role in stimulating creative thinking, analytical skills and independent research activity of students is identified. Prospects for introducing such technologies into the system of work with gifted children are outlined.